Achievement of conceived level of change of high school student as effect of video supported conceptual change text (vscctext) in teaching remedial concept boil - F Ulya; A Suhandi; A Samsudin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to construct and test the use of Video Supported Conceptual Change Text (VSCCText) to assist the conceptual change level of high school students in remedial teaching on boiling concepts. This research utilizes pre-experiment method with one group pretest-posttest design. The subjects of the research were the students of class XI in one of the senior high schools in Bekasi regency. The levels of conceptual change reviewed include; level of scientific conception from the start, construction level, reconstruction level, static level, and disorientation level. The analysis conceptual change level has been described that the total subjects is 10% of students were at the scientific conception level from the beginning, 20% of students were at construction level, 55% of students were at reconstruction level, 15% of students were at static level and 0% of students were at disorientation level. If calculated from the number of students who initially experienced misconceptions and did not have a preliminary conception, then got the number 82% of students are in the type of conceptual change of construction and reconstruction. To sum up, the use of VSCCText has a high effectiveness in facilitating the achievement of conceptual change level of construction and reconstruction.